Utilization of Telehealth in Improving the Quality of Health Services During the Pandemic: Systematic Review - Khaeratunnafisah, Khaeratunnafisah; Lizbeth, Karani (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aims to determine the use of telehealth in health services during the pandemic, and to determine the types of platforms used in health services during the pandemic.Methodology: This study is a review using the Systematic Review method using the PRISMA 2009 checklist guidelines which was then followed by the Critical Appraisal Skills Programme (CASP).Main Findings: A total of 10,384 articles were identified from four types of database searches, namely Pubmed, Scopus, Science Direct, and Proquest, which had been filtered with a publication limit of the last 3 years (2019-2021). However, after screening, 9,750 articles were found that did not match the research questions and objectives, leaving 10 articles that were similar to the research topic.Novelty/Originality of this study: This study presents novelty by systematically summarizing various recent findings related to the use of telehealth as an innovative strategy in improving the quality of health services during the pandemic, especially in overcoming limited access and direct interaction between medical personnel and patients.